The Urgency Of Public Communication Ethics In The Era Of Cyber Society - Nasiratunnisaa Mallappiang (LAFADZ JAYA Publisher, 2022)
The development of communication technology with various new media platforms forms a new society called Cyber Society. The massive digital content consumed by the cyber community causes frequent interruptions in communication and disharmony due to lack of responsibility and communication ethics. This research is qualitative research using a literature review. Based on the results of this study, ethics plays a very important role in communication in the cyber era. Using communication ethics can prevent cyber crimes that harm yourself and others. Internet ethics must be applied in cyberspace society, starting from oneself, family and those closest to them, and learning to use the internet safely and responsibly. the occurrence of violations of the law contained in Law Number 19 of 2016 amendment to Law Number 11 of 2008 concerning Information and Electronic Transactions. A prison sentence with a fine of hundreds of millions to billions of rupiah awaits if you violate the ethics of communication in cyberspace.